Translanguaging in Clinical Communication at Khodijah Mother and Child Hospital and Its Implications for English for Specific Purposes Curriculum in Vocational Schools - Firdaus, Adi; Mushthoza, Dina Amaliyah (Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines translanguaging practices in multilingual clinical communication and explores their implications for English for Specific Purposes (ESP) curriculum development in Indonesian vocational schools. While previous research has addressed translanguaging, healthcare communication, and ESP pedagogy separately, limited attention has been given to how English medical terminology, Indonesian, and local languages operate as an integrated communicative repertoire in authentic clinical workplaces or how such practices inform vocational ESP design. Drawing on sociolinguistic and translanguaging perspectives, this descriptive qualitative case study investigates how healthcare professionals at a maternal and child hospital in East Java strategically mobilize English medical terminology, Indonesian, and Javanese across multiple clinical units. Data were collected through semi-structured interviews with six healthcare professionals and analyzed thematically to identify recurrent communicative patterns. The findings demonstrate that translanguaging functions as a systematic, institutionally embedded practice rather than incidental language mixing: English serves as a resource for biomedical precision, Indonesian mediates procedural explanation, and Javanese supports interpersonal and affective alignment, particularly in high-vulnerability contexts. Beyond practical implications for curriculum development, the study contributes theoretically by extending translanguaging scholarship into professional healthcare discourse and by reconceptualizing multilingual competence as a legitimate communicative resource within ESP-oriented vocational education. The study further advances ESP discussions by proposing a translanguaging-informed perspective for vocational English curriculum development grounded in authentic multilingual workplace practices and advancing translanguaging as a framework for professional communication in ESP contexts.